The Potential Of Natural Product Enrichment Noodle In Improving The Health Of Pregnant Women - Juliana Christyaningsih; Laili Rahmawati; Nur Hatijah; Muhammad Andy Firmansyah (Politeknik Kesehatan Kemenkes Surabaya, 2026)
Pregnancy is a critical period in which adequate nutrition is essential for both maternal and fetal health. This study aimed to evaluate the effect of natural product-enriched noodles, combining snakehead fish (Channa striata), Moringa oleifera leaves and okra (Abelmoschus esculentus), on the hemoglobin, hematocrit, and blood protein levels of pregnant women with chronic energy deficiency (CED). Stunting remains a significant public health problem in Indonesia, with a prevalence of 28.9% in Surabaya in 2021. Protein deficiency and anemia during pregnancy increase the risk of intrauterine growth restriction, low birth weight, and stunting. It was hypothesized that the combined nutritional properties of these ingredients — high protein and albumin from snakehead fish, iron and antioxidants from Moringa, and bioactive compounds from okra would synergistically improve maternal nutritional status. A Pre-Experimental One Group Pretest-Posttest Design was employed at Sidosermo Community Health Center, Surabaya, from June to September 2025. All 15 eligible pregnant women with CED at the study site were enrolled using total sampling (n=15); the small sample size and absence of a control group represent key study limitations affecting generalizability and causal inference. Participants consumed protein-enriched noodles made from modified cassava flour, snakehead fish, Moringa leaves, and okra three times per week for one month, a frequency and dose based on prior food-based supplementation programs in pregnant women. The noodle product was confirmed to be high in protein (14.22%) and microbiologically safe. Post-intervention, the number of anemia cases decreased from 11 to 4 participants, hematocrit normalized in 4 of 11 previously low cases, and blood protein levels normalized in 10 of 15 participants. As no inferential statistical analysis was performed, these findings should be interpreted with caution. These results suggest that locally sourced nutritional interventions have the potential to improve maternal nutritional status and contribute to reducing stunting prevalence in Indonesia.